Rapid and sustained containment of covid-19 is achievable and worthwhile: implications for pandemic response. (1st December 2021) - Chen, Qiulan; Rodewald, Lance; Lai, Shengjie; Gao, George F
Abstract : Qiulan Chen and colleagues argue that innovative technological and organisational approaches can overcome important challenges to containment measures early in a pandemic